1987
DOI: 10.1099/00221287-133-3-773
|View full text |Cite
|
Sign up to set email alerts
|

Isolation from Urine of Two Serratia marcescens Strains Excreting a Diffusible Yellow Pigment

Abstract: Two bacterial strains excreting a yellow pigment were isolated from human urine and identified as Serratia marcescens. The pigment was produced in the late exponential and early stationary phases of growth. Minimal media supplemented with tyrosine, phenylalanine, 3,4-dihydroxyphenylacetate or tryptophan, as well as complex media, induced pigment production. UVvisible spectra of the extracted pigment had peaks characteristic of 2-hydroxy-5-carboxymethylmuconate semialdehyde, produced from meta-cleavage of 3,4-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1988
1988
2000
2000

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…Among bacteria, eurnelanins have been demonstrated in Actinomycetes (Kiister 1976) and factors than pigmented ones, which could be an advantage in clinical environments (Ding and Williams 1983;Platt and Sommerville 1981 ;Quian et al 1982). Recently, we described two S. marcescens strains that excreted a yellow diffusible pigment, 2-hydroxy-5-carboxymethylmuconic acid semialdehyde, which is related to the catabolism of tyrosine in this species (Trias et al 1987a(Trias et al , 1988. While studying the induction of the yellow pigment in nonpigmented strains of S. marcescens isolated from human infections, we found that sometimes brown pigmentation appears in the culture medium.…”
Section: Introductionmentioning
confidence: 95%
See 4 more Smart Citations
“…Among bacteria, eurnelanins have been demonstrated in Actinomycetes (Kiister 1976) and factors than pigmented ones, which could be an advantage in clinical environments (Ding and Williams 1983;Platt and Sommerville 1981 ;Quian et al 1982). Recently, we described two S. marcescens strains that excreted a yellow diffusible pigment, 2-hydroxy-5-carboxymethylmuconic acid semialdehyde, which is related to the catabolism of tyrosine in this species (Trias et al 1987a(Trias et al , 1988. While studying the induction of the yellow pigment in nonpigmented strains of S. marcescens isolated from human infections, we found that sometimes brown pigmentation appears in the culture medium.…”
Section: Introductionmentioning
confidence: 95%
“…Mutant enrichment was performed by a modification of the azthreonam mutant enrichment method (Trias et al 1987b). The mutagenized cells were pelleted and resuspended in Erlenmeyer flasks with 50 mL of M70 medium (Grimont and Grimont 1984), with tyrosine as the sole carbon and energy source.…”
Section: Isolation and Characterization Of Mutantsmentioning
confidence: 99%
See 3 more Smart Citations